2020
DOI: 10.1021/acs.energyfuels.0c03349
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Trends for Total Vanadium Content and Vanadyl Porphyrins in Gel Permeation Chromatography Fractions Reveal Correlations between Asphaltene Aggregation and Ion Production Efficiency in Atmospheric Pressure Photoionization

Abstract: Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) has exposed the ultracomplexity of fossil fuels, thereby validating the compositional trends that rule petroleum distillation, known as the Boduszynski Continuum. Routine FT-ICR MS analysis of a single crude oil sample can reveal tens-of-thousands of unique molecular formulas; however, currently available ionization methods suffer from limitations for such complex mixtures that are not yet completely understood. Simply put, MS detects ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 103 publications
2
52
0
Order By: Relevance
“…Our results confirm that nanoparticles not only reduce the amount of asphaltenes in solution but also decrease the size of the asphaltene aggregates in the remaining solution by adsorbing the most unstable and larger nanoaggregates. Interestingly, the GPC-ICP MS Vanadium chromatogram of the samples G and H, with a signal starting from 1260s is very similar with the results reported in our previous works 37,43 , for acetone fraction, with a GPC-ICP MS chromatogram starting at 22.5min (1272s) and presenting 3 maximums (23.2 min =1400s, 25.5min=1530s and 28.5=1710s). This acetone fraction also showed a very low tendency to form deposit on the quartz surface, and the FT-ICR MS analysis proved that it presents a higher aromaticity and more island-like structure than the other fractions (Hep/Tol and Tol/THF/MeOH).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results confirm that nanoparticles not only reduce the amount of asphaltenes in solution but also decrease the size of the asphaltene aggregates in the remaining solution by adsorbing the most unstable and larger nanoaggregates. Interestingly, the GPC-ICP MS Vanadium chromatogram of the samples G and H, with a signal starting from 1260s is very similar with the results reported in our previous works 37,43 , for acetone fraction, with a GPC-ICP MS chromatogram starting at 22.5min (1272s) and presenting 3 maximums (23.2 min =1400s, 25.5min=1530s and 28.5=1710s). This acetone fraction also showed a very low tendency to form deposit on the quartz surface, and the FT-ICR MS analysis proved that it presents a higher aromaticity and more island-like structure than the other fractions (Hep/Tol and Tol/THF/MeOH).…”
Section: Discussionsupporting
confidence: 88%
“…The column calibration was only used to verify the performance of the columns and not to determine the MW of the asphaltenes, due to the difference in complexity between the polymer standards and asphaltene's matrix. However, in our previous publications we have shown that HMW size distribution are primarily aggregate compounds, while LMW are "free" compounds, and MMW a mixture of "free" and aggregate compounds 34,36,37 .…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…112 Qian et al 38 further reported a wide diversity of petroporphyrin structures that contain multiple sulfur and oxygen atoms (CcH2c+zN4VOoSs) in vacuum residue using APPI FT-ICR MS. 38 The first comprehensive characterization of vanadyl porphyrins in unfractionated heavy petroleum and virgin asphaltenes using APPI FT-ICR MS was performed by McKenna et al 31 The authors highlight the need for FT-ICR MS to achieve unambiguous molecular formula assignment (˂300 ppb) and document the likelihood of misassigning vanadyl porphyrin peaks (N4O1 51 Vanadyl porphyrins have been detected in asphaltenes isolated from vacuum gas oil distillate cuts and in pentane, in-between C5C7 asphaltenes, and heptane asphaltenes using APPI FT-ICR MS. 113,114 Additional studies have applied APPI FT-ICR MS to asphaltene extrography fractions and highlight structural characterization using infrared multiphoton dissociation (IRMPD), confirming the dominance of single core vanadyl porphyrin structures. 84 Supercritical fluid extraction and fractionation (SFEF) of Venezuelan Orinoco extra heavy crude vacuum residue concentrates vanadyl porphyrins in high boiling end cuts detected using APPI FT-ICR MS. 66 Furthermore, Chacón-Patiño et al 115 investigated the molecular composition of vanadyl porphyrins in PetroPhase 2017 asphaltenes and extrography fractions, with a specific focus on the molecular composition of vanadyl porphyrins as a function of the aggregate size distribution, using GPC ICP-MS and online GPC APPI FT-ICR MS at 21 tesla (Figure 5). The authors performed quantitative detection of vanadium using GPC ICP-MS and concluded that the majority of the vanadyl porphyrin ions are produced from later eluting GPC fractions (low aggregation LMW part) and that highly aggregated fractions contain abundant porphyrins with much longer homologous series than those species from the less aggregated GPC fractions.…”
Section: ■ Ionization Techniques For Ms Of Metalloporphyrinsmentioning
confidence: 99%
“…Heavy oils have a considerable amount of asphaltene-resinous components, heteroatoms (S, N, and O), and metals (vanadium and nickel) . The asphaltenes in heavy oils contain iron, vanadium, and nickel (up to 1%), of which the proportion of vanadium is more than 80%. , Vanadylporphyrins, one of the most common forms of crude oil metalloporphyrins, play an important role in asphaltene aggregation, fouling, and deposition. …”
Section: Asphaltene Structurementioning
confidence: 99%